Sam Elliott double feature Gone to Texas and Blue River - Elliott, Sam, 1944-; Beck, Michael, 1949-; O'Connell, Jerry, 1974-; Stahl, Nick, 1979-; McDonough, Neal.; Barnwell, Jean Marie; Renna, Patrick; Dey, Susan, 1952-; Elikann, Larry S.; Canan, Ethan; Echo Bridge Home Entertainment; Signboard Hill Productions ([La Crosse, Wis.] : Echo Bridge Home Entertainment, 2010)
Gone to Texas: The true-life story of Sam Houston, the frontier hero and statesman whose bravery and vision led to the creation of the Republic of Texas. Blue River: Based on the novel by Ethan Canin, Blue River depicts the powerful events that unfold in a small Wisconsin town driving 2 teenage brothers apart when later in life one brother, now a homeless derelict, arrives at the home of his brother, now a successful doctor.
Gone to Texas originally produced for CBS television in 1986. Blue River originaly produced for Hallmark Hall of Fame in 1995.
Blue River based on the novel by Ethan Canan.
Blue River: music by Lawrence Shragge ; production designer, Donald Lee Harris ; director of photography, Eric Van Haren Homan ; edited by Sabrina Plisco-Morris ; produced by Brent Shields ; executive producer Richard Welsh ; teleplay by Maria Nation ; directed by Larry Elikann. Gone to Texas: producer, Frank Q. Dobbs ; teleplay, John Binder ; director, Peter Levin.
Sam Elliott, Michael Beck, Jerry O'Connell, Nick Stahl, Neal McDonough, Jean Marie Barnwell, Patrick Renna, Susan Dey.
Gone to Texas: Not rated. Blue River rated PG-13.
DVD.
Keywords: Houston, Sam, -- 1793-1863 -- Drama; Families -- Drama; Brothers -- Drama; Texas -- History -- Drama; Made-for-TV movies; Television plays; Historical films; Feature films; Biographical films; Western films